Estimating the prevalence of exclusive breastfeeding with data from household surveys: Measurement issues and options - Pullum, Thomas W.; Gribble, Karleen; Mihrshahi, Seema; Borg, Bindi (Frontiers in Nutrition, 2023)
The importance of breastfeeding for infant and maternal health is well established. The World Health Organization recommends that all infants be exclusively breastfed until they reach six months of age. The standard indicator to measure adherence to this criterion is the percentage of children aged 0-5 months who are currently being exclusively breastfed. This paper proposes supplementary measures that are easily calculated with existing survey data. First, for an accurate assessment of the WHO recommendation, we estimate the percentage of infants who are being exclusively breastfed at the exact age of six months. Second, an adjustment is proposed for prelacteal feeding. These two modifications, separately and in combination, are applied to data from 31 low- and middle-income countries that have participated in the Demographic and Health Surveys Program since 2015. There is considerable variation in the effects across countries. The modifications use existing data to provide a more accurate estimate than the standard indicator of the achievement of the exclusive breastfeeding until six months recommendation.